Will you solve for θ \theta ?

Geometry Level 3

If ( 1 + sin θ ) ( 1 + cos θ ) = 5 4 \left( 1+ \sin \theta \right) \left( 1+ \cos \theta \right) = \dfrac{5}{4} , then what is the value of ( 1 sin θ ) ( 1 cos θ ) \left( 1- \sin \theta \right) \left( 1- \cos \theta \right) ?

4 10 7 4 \frac{4\sqrt {10}-7}{4} 13 + 4 10 4 \frac{13+4\sqrt {10}}{4} 13 4 10 4 \frac{13-4\sqrt {10}}{4} 4 10 + 7 4 \frac{4\sqrt {10}+7}{4}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Tapas Mazumdar
Sep 4, 2016

Let ( 1 sin θ ) ( 1 cos θ ) = x \left( 1- \sin \theta \right) \left( 1- \cos \theta \right) = x .

Now, upon expanding all terms we get,

( 1 + sin θ ) ( 1 + cos θ ) = 1 + sin θ + cos θ + sin θ cos θ = 5 4 \left( 1+ \sin \theta \right) \left( 1+ \cos \theta \right) = 1+ \sin \theta + \cos \theta + \sin \theta \cos \theta = \dfrac{5}{4} . . . ( 1 ) ...\left( 1 \right)

( 1 sin θ ) ( 1 cos θ ) = 1 sin θ cos θ + sin θ cos θ = x \left( 1- \sin \theta \right) \left( 1- \cos \theta \right) = 1- \sin \theta - \cos \theta + \sin \theta \cos \theta = x . . . ( 2 ) ...\left( 2 \right)

Adding ( 1 ) \left( 1 \right) and ( 2 ) \left( 2 \right) , we get,

2 + 2 sin θ cos θ = 5 4 + x 2 + 2\sin \theta \cos \theta = \dfrac{5}{4} + x

\large \therefore sin θ cos θ = 4 x 3 8 \sin \theta \cos \theta = \dfrac{4x-3}{8} . . . ( 3 ) ...\left( 3 \right)

Multiplying ( 1 ) \left( 1 \right) and ( 2 ) \left( 2 \right) , we get,

( 1 sin 2 θ ) ( 1 cos 2 θ ) = 5 4 x \left( 1- \sin^{2} \theta \right) \left( 1- \cos^{2} \theta \right) = \dfrac{5}{4} x

\large \therefore sin 2 θ cos 2 θ = 5 4 x \sin^{2} \theta \cos^{2} \theta = \dfrac{5}{4} x . . . ( 4 ) ...\left( 4 \right)

From ( 3 ) \left( 3 \right) and ( 4 ) \left( 4 \right) , we get,

( 4 x 3 8 ) 2 = 5 4 x {\left( \dfrac{4x-3}{8} \right)}^{2} = \dfrac{5}{4} x

Solving for x x , we get,

x = 13 ± 4 10 4 x = \dfrac{13 \pm 4\sqrt{10}}{4}

From ( 4 ) \left( 4 \right) , we have,

sin 2 θ cos 2 θ = 5 4 x \sin^{2} \theta \cos^{2} \theta = \dfrac{5}{4} x

x = 4 5 sin 2 θ cos 2 θ \Longrightarrow x = \dfrac{4}{5} \sin^{2} \theta \cos^{2} \theta

x \therefore x can have a maximum value of 1 5 \dfrac{1}{5} . ( W h y ? ) \left( Why? \right)

So, from the values of x x we got upon solving the quadratic equation only x = 13 4 10 4 x = \boxed {\dfrac{13 - 4\sqrt{10}}{4}} satisfies the criteria.

Clever method. :)

Brian Charlesworth - 4 years, 9 months ago

Log in to reply

Thank you sir! 😊

Tapas Mazumdar - 4 years, 9 months ago
Steven Chase
Sep 4, 2016

One way to solve it would be to solve for θ \theta . I used a different technique and got a bit lucky.

( 1 s i n 2 θ ) ( 1 c o s 2 θ ) = ( 1 s i n θ ) ( 1 + s i n θ ) ( 1 c o s θ ) ( 1 + c o s θ ) (1-sin^{2}\theta)(1-cos^{2}\theta) = (1-sin\theta)(1+sin\theta)(1-cos\theta)(1+cos\theta)

( c o s 2 θ ) ( s i n 2 θ ) (cos^{2}\theta)(sin^{2}\theta) = 5 4 ( 1 s i n θ ) ( 1 c o s θ ) \frac{5}{4}(1-sin\theta)(1-cos\theta)

4 5 ( c o s 2 θ ) ( s i n 2 θ ) \frac{4}{5}(cos^{2}\theta)(sin^{2}\theta) = ( 1 s i n θ ) ( 1 c o s θ ) (1-sin\theta)(1-cos\theta)

Since s i n θ sin\theta and c o s θ cos\theta can be no larger than 1 1 , LHS can be no larger than 4 5 \frac{4}{5} . As it turns out, there is only one option in the list that is smaller than 4 5 \frac{4}{5}

Prakhar Bindal
Oct 20, 2016

Let (1-sinx)(1-cosx) = y

1-sinx-cosx+sinxcosx=y

We are given 1+sinx+cosx+sinxcosx = 5/4

Subtract these to get 5/4 - y = 2(sinx+cosx)

Now (1+sinx)(1+cosx) = 5/4

We know 1+cosx = 2cos^2(x/2)

1+sinx = (sinx/2 + cosx/2)^2

Substituting and simplifying

We get 5/2 = (sinx+cosx+1)^2

From here sinx+cosx can be found out and thats what we require

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...